Análise do programa Reciclando Cidadão: contribuição para o meio ambiente e para a renda familiar dos catadores no município de Cruzeiro do Oeste – PR - Conceição, Lucas Garbugio (2018)
The objective of this work was to analyze how the “Programa Reciclando Cidadão” contributes to the environment and to the family income of waste pickers in the Municipality of Cruzeiro do Oeste – Paraná. For this, it was necessary to describe the importance of the recycling process for the environment and for the municipal waste pickers, to present the program’s operation, to address how much recyclable solid waste was collected and to analyze the income and expenses of the association. The work was carried out through Bibliographic Research in publications and documents made available by the “Secretaria Municipal de Meio Ambiente de Cruzeiro do Oeste – PR. The analysis of the data was done through reading, interpretation and elaboration of graphs and tables that classify and compare the information collected. After analyzing the data, it was verified that the “Programa Reciclando Cidadão” has its environmental importance of importance, since it removes the waste that would be destined to the landfill through reuse. These are sold and reused. The sale assists in obtaining resources that maintain the association and provide family income to the associated scavengers.